2010
DOI: 10.4038/cmj.v49i4.1920
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of schoolchildren in an urban area of Sri Lanka

Abstract: Background As in many other Asian countries, Sri Lanka is in the phase of a rapid demographic, nutritional and epidemiological transition. As a result dietary habits and lifestyle are changing. These have led to new health problems in the region. Childhood overweight and obesity are examples of such problems.Objective To provide information on the nutritional status of 8-12 years old schoolchildren in an urban area of Sri Lanka.Subjects and methods Seven schools situated in the city of Colombo were randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 2 publications
10
65
3
Order By: Relevance
“…The students attending private schools are with a good socioeconomic status and their nutritional status had always been better than the students attending public schools [21]. The present study compared nutritional status of school children in the public and private primary schools in Zagazig city were compared, the results showed that there was a significant difference between them regarding the BMI, children in private primary school had a higher mean value of 28.4±8.8 kgm than that of the children of public primary school who had a mean value of 24.7 ± 7.1 kgm.…”
Section: Discussionmentioning
confidence: 99%
“…The students attending private schools are with a good socioeconomic status and their nutritional status had always been better than the students attending public schools [21]. The present study compared nutritional status of school children in the public and private primary schools in Zagazig city were compared, the results showed that there was a significant difference between them regarding the BMI, children in private primary school had a higher mean value of 28.4±8.8 kgm than that of the children of public primary school who had a mean value of 24.7 ± 7.1 kgm.…”
Section: Discussionmentioning
confidence: 99%
“…In Sri Lanka, a nutrition study among children of age 8-12 years showed that the prevalence of obesity in boys was 4.3% and in girls was 3.1%. 9 In Sri Lankan students, thinness was 24.7% in boys and 23.1% in girls. So, our children had more undernutrition than that of Sri Lanka though obesity was somehow lower.…”
mentioning
confidence: 99%
“…Also, Olivares S. et al (2004) indicated that before using the dietary curriculum at the school, the prevalence of obesity and overweight were 15.4% and 19.6% respectively (17). The results of a study conducted by Wickramasingh VP et al (2004) also showed higher prevalence of obesity among boys (4.3%) than in girls (3.1%) (18). Another study reported higher obesity rate (5.5%) and overweight (5.0%) among boys compared with girls of whom 2.0% were obese and 3.5% overweight (19).…”
Section: Discussionmentioning
confidence: 93%